The Methods, The Principles and The Possibility of using the Tandem 5 SDH-2 PELLETRON static accelerator in the same way as the SMA particle accelerator to determine the ages of the antiquities by C-14. - PHIPHATPHON , Soulasay; QUÔC Hùng, Ph.D. PHAM (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This study expored the methods and principles to determine the ages of the existing expired lifespan antiquities by C-14. Also, il inverstigated de development of measurement tool (C-14) to be more accurate, precise, detailed time saving and convenient. The equipment that was available in the laboratory was used in different ways and maximize their usefulness.The objectives of this study were to discover the age of the antiquities by C-14 and to study the possibility of using the Tandem 5SDH-2 PELLETRON static accelerator in the same way as the SMA particle accelerator to determine the ages of the antiquities by C-14. The instrument of this study was the Tandem 5SDH-2 Pelletron electrostatic accelerator laboratory, Department of Nuclear Physics, University of Natural Science, Hanoi and the methods of study were relevant theories of C-14 from newspapers, scientific journals, textbooks in the library, the geology department, the physics department, the 14-C Laboratory of the Institute of Archeology Hanoi. The results of this study revealed knowledge and understanding to determine the age of the antiquities. The study used C-14 to diccover the quantityof existing atom C-14 that contain in selected lifespan antiquities in order to compare with the quantity of atom in living antiquities. The results also disclosed the convenience, difficulty, advantages, and limitation in applying C-14 method. The highlight of the study was the feasibility of using the Tandem 5SDH-2 PELLETRON from the Nuclear Physics Laboratory at the University of Natural Sciences in Hanoi as a particle accelerator to reach C-14 in the next step level is possible in principle. But, from the point of view of efficiency, reality and economy, the best answer is therefore "no".